EVALUASI KETAHANAN TANAMAN JERUK (Citrus sp.) HASIL FUSI PROTOPLAS JERUK SATSUMA MANDARIN (Citrus unshiu) DAN JERUK SIAM MADU (Citrus nobilis) TERHADAP INFEKSI PENYAKIT KULIT DIPLODIA (Botryodiplodia theobromae Pat.) - Dharmawan Putra; Liliek Sulistyowati; Abdul Cholil; C Martasari (Jurnal HPT (Hama Penyakit Tumbuhan), 2013)
ABSTRACTProtoplast fusion mandarin satsuma orange and honey thai orange to increase thequality of the honey thai orange into a seedless. Character of orange as product ofprotoplast fusion has not been known include resistance against pest and disease.One important disease of citrus is skin disease of diplodia that cause loosing yield.Protoplast fusion has highly genetic variability that cause many probabilities ofresistance expression can be happened on infection of skin disease of diplodia onorange as product of protoplast fusion. Research was conducted at glass house ofBALITJESTRO and Phytopathology Laboratory, Department of Plant Protection,Faculty of Agriculture, University of Brawijaya. The purpose of this research wasto evaluation of resistance of orange as product of protoplast fusion and itsparental on infection of skin disease of diplodia by incubation period and infectionsymptom area. Result of this research were known that there were 26 oranges asproduct of protoplast fusion had different resistance level compared by its parentalin incubation period; there were 16 oranges as product of protoplast fusion haddifferent resistance level compared by its parental in infection symptom area andthere were 11 oranges as product of protoplast fusion had not different resistancelevel compared by its parental in infection symptom area; Classification of theresistance level of oranges as product of protoplast fusion were obtained 8 plantswere classified resistant, 17 plants were classified moderate, 5 plants wereclassified susceptible.Keywords: Plant endurance, Protoplast fusion, Citrus unshiu, Citrus nobilis,Botryodiplodia theobromae Pat.